Upaya Meningkatkan Kemandirian Anak Melalui Metode Bermain Peran Berbasis Practical Life Pada Kelompok A di TK Satu Atap Neglasari Kecamatan Kalibunder Kabupaten Sukabumi - Rinawati, Rinawati; Hurri, Ibnu; Awal Maulana, Redi (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This study aims to improve children's independence through role-playing methods based on practical life in group A at TK Satu Atap Neglasari, Kalibunder District, Sukabumi Regency. The research method used is Classroom Action Research (CAR) with the Kemmis and McTaggart spiral model, consisting of two cycles. Each cycle includes planning, implementation, observation, and reflection. The results showed that the role-playing method based on practical life was effective in increasing children's independence, especially in decision-making, completing simple tasks, and responsibility. In cycle I, children's independence increased by 20%, and in cycle II, it increased to 40%. The conclusion of this study is that the role-playing method based on practical life can be an effective learning alternative to improve early childhood independence.